2017
DOI: 10.1007/s11011-017-0088-z
|View full text |Cite
|
Sign up to set email alerts
|

Ketogenic diet versus gluten free casein free diet in autistic children: a case-control study

Abstract: UMIN-CTR Study Design: trial Number UMIN000021433.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
102
2
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 109 publications
(115 citation statements)
references
References 22 publications
6
102
2
5
Order By: Relevance
“…In the present study, we obtained data from 10 participants that maintained the diet past the 3-month time point and found the improvements in social behavior are maintained. Moreover, our findings of significant improvement in CARS-2 scores after 3 months on our modified KD are in agreement with a recent case control study in 45 children that found significant improvement in CARS scores after 6 months on the modified Atkins diet [15]. Taking into account this case control study and our study, both studies suggest that a specific component of a KD may mediate the beneficial effects for ASD behavior.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In the present study, we obtained data from 10 participants that maintained the diet past the 3-month time point and found the improvements in social behavior are maintained. Moreover, our findings of significant improvement in CARS-2 scores after 3 months on our modified KD are in agreement with a recent case control study in 45 children that found significant improvement in CARS scores after 6 months on the modified Atkins diet [15]. Taking into account this case control study and our study, both studies suggest that a specific component of a KD may mediate the beneficial effects for ASD behavior.…”
Section: Discussionsupporting
confidence: 92%
“…After 3 months on the modified KD/GF/MCT, approximately 50% showed moderate to substantial improvement in ADOS-2 scores. In agreement with previous studies, we did not observe significant relationships between BHB levels and the degree of improvement in ASD symptoms [14,15]. The degree of improvement (20%) represented moderate changes in ADOS-2 scores.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In the BTBR mouse model of ASD, a ketogenic diet improved symptoms by increasing sociability and decreasing self-directed repetitive behaviour 174 . It was recently reported that a ketogenic diet also improves symptoms in children with ASD 175 . As yet, trials of IF in ASD have not been performed.…”
Section: Ims and Neurological Disordersmentioning
confidence: 97%